Analysis of a Cable Stayed Bridge with Different Pylon Types: A Review - Singh, Avinash; Malviya, Pratiksha (International Journal of Scientific Research in Civil Engineering, 2018)
The study of the bridge section superstructure has analyzed using analysis software (STAAD.Pro) which is a traditional type use in bridges.we will discusse the advantages of the bridge in the construction point of view. Bridge sections is a simple, easy and fast construction type of structure and world wide it has using for span length 262 m. A literature review is an evaluative report of studies found in literature related to selected area. The literature related to selected area. The literature review should describe, summarize, evaluate, and clarify the literature. A literature review goes beyond the search for information and includes the identification and articulation of relationship between the literature and field of research. While the form of literature review might be vary with various types of studies. We have different literature review from papers, journals, websites and dissertation.